Iron curtains : gates, suburbs, and privatization of space in the post-socialist city - Hirt, Sonia (Wiley Online Library., 2012)
Utilizing research conducted primarily with residents of Sofia, Bulgaria, Iron Curtains: Gates, Suburbs, and Privatization of Space in the Post-socialist City explores the human dimension of new city-building that has emerged in East Europe.Features original data, illustrations, and theory on the process of privatization of resources in societies undergoing fundamental socio-economic transformations, such as those in Eastern EuropeRepresents the sole in-depth monograph on contemporary urbanism in Southeast EuropeMakes a broader statement on issues of urbanism in Europe and other parts of the world while highlighting the complex connections between cultures and cities.